THE STUDENT LEXICAL ERRORS IN WRITING SPOOF ESSAY AT ELEVENTH GRADE OF YAYASAN ISLAMIC CENTER NORTH SUMATERA - Tanjung, Humairah (BRIGHT VISION Journal of Language and Education, 2021)
The purpose of this study was to determine the student Lexical Errors in Writing Spoof Essay at Eleventh Grade of Yayasan Islamic Center Sumatera Utara in academic year of 2020/2021. To find out what errors in writing spoof essay can occur and to find out how and why these errors can occur in student writing spoof essays. The focus of this research is Lexical Errors in Writing Spoof Essay at Eleventh Grade. The method used in this research is descriptive qualitative. The research data was carried out on essays written by students. The steps for error analysis are collecting data from student writing essay, identified and classified the errors contained in the lexical errors in writing spoof essays. The data analysis process is described based on Dulay in Kuntjara (2013: 2). From the research results it can be seen that the errors made by the students in writing are omission, addition, misformation,  misordering, misspelling, semantically. This error can occur due to various processes based on the type of error, including errors that can occur due to L1 to L2 influence, intra- language disorders, limited knowledge of English grammar, lack of mastering vocabulary in English, and errors in understanding the meaning of words that are almost similar the pronunciation and writing in English.Keywords: Spoof Essay, Writing, Lexical Errors